Revision of the New World genera Adelius Haliday and Paradelius de Saeger (Hymenoptera: Braconidae: Cheloninae: Adeliini) - Shimbori, Eduardo M.; Bortoni, Marco A.; Shaw, Scott R.; Souza-Gessner, Carolina Da S.; Cerântola, Paula De C. M.; Penteado-Dias, Angélica M. (Zootaxa, 2019)
Species of adeliine braconids were previously described and named from all biogeographic areas of the world except the Neotropical Region. Here we present the first taxonomic revision of New World adeliines, as well as the first newly described species of both genera, Adelius and Paradelius, from the Neotropical Region. Although not commonly sampled because of their minute size and associations with leaf-mining hosts, our results indicate that adeliines actually have a wide distribution in the neotropics, especially in middle to high elevations and dry forests. In addition to redescriptions of all known Nearctic species, we present the first descriptions of the females of Adelius coloradensis and A. nigripectus, of 16 new species of the genus Adelius (A. adeleae Shimbori & Shaw sp. n., A. bolivariensis Bortoni & Penteado-Dias sp. n., A. boliviensis Bortoni & Penteado-Dias sp. n., A. caatinga Bortoni, Shimbori & Penteado-Dias sp. n., A. canadensis Shimbori & Shaw sp. n., A. ecuadoriensis Bortoni & Penteado-Dias sp. n., A. excelsus Bortoni & Shimbori sp. n., A. floridensis Shimbori & Shaw sp. n., A. gauldi Shimbori & Shaw sp. n., A. janzeni Shimbori & Shaw sp. n., A. monteiroi Souza-Gessner, Cerântola & Penteado-Dias sp. n., A. morretesiensis Bortoni, Shimbori & Penteado-Dias sp. n., A. panamensis Shimbori & Shaw sp. n., A. pentagonalis Shimbori & Shaw sp. n., A. quiteriae Souza-Gessner, Cerântola & Penteado-Dias sp. n., and A. sancticaroli Bortoni, Penteado-Dias & Shimbori sp. n.), and one new species of the genus Paradelius (P. neotropicalis Shimbori & Shaw sp. n.). Keys for the New World species of both genera are provided.